Polip endometrium pada sapi bunting tua - Yusuf, Anang; Widiyatno, Thomas Valentinus; Samik, Abdul (Universitas Airlangga, 2021)
The current report describes acute death in 8.5 months pregnant cow, which no signs of illness before. Postmortem examination showed the presence of gastric bloat. Necropsy revealed no change in the viscera, but yellow and cloudy nodules were found on the endometrial wall, amniotic fluid mixed with blood, blood clots in the inner cervical canal, pneumonia in the lungs. Meanwhile, the anatomical condition of the fetus was normal. It could be concluded that the cow's sudden death was due to late pregnancy, causing high tension that triggers rupturing of the polyp blood vessels. The deep vein thrombosis due to late pregnancy causes pulmonary emboli and subsequent pneumonia.